If fx) = 3* + 10x and x) = 4x - 2, find (f+ g)(x).
![If fx 3 10x and x 4x 2 find f gx class=](https://us-static.z-dn.net/files/d60/202603dfe256104f415c84e086c83128.jpg)
Answer:
[tex]\boxed {\boxed {\sf B. \ 3^x + 14x-2}}[/tex]
Step-by-step explanation:
We are given 2 functions:
We are asked to find (f+g)(x) or f(x)+ g(x). Essentially, we are finding the sum of the functions.
[tex](f+g)(x)=f(x)+ g(x)[/tex]
[tex](f+g)(x)=(3^x + 10x) + (4x-2)[/tex]
[tex](f+g)(x)= 3^x + 10x + 4x -2[/tex]
Simplify the expression by combining like terms. There are 2 terms with a variable of x, so they can be added together.
[tex](f+g)(x)= 3^x + ( 10x + 4x) -2[/tex]
[tex](f+g)(x)= 3^x + 14x -2[/tex]
The sum of the functions f(x) and g(x) is 3ˣ + 14x -2 and choice B is correct.